Redox Regulation of PPARγ in Polarized Macrophages. (1st July 2020) - Trümper, Verena; Wittig, Ilka; Heidler, Juliana; Richter, Florian; Brüne, Bernhard; von Knethen, Andreas
Abstract : The peroxisome proliferator-activated receptor (PPAR γ ) is a central mediator of cellular lipid metabolism and immune cell responses during inflammation. This is facilitated by its role as a transcription factor as well as a DNA-independent protein interaction partner. We addressed how the cellular redox milieu in the cytosol and the nucleus of lipopolysaccharide (LPS)/interferon- γ - (IFN γ -) and interleukin-4- (IL4-) polarized macrophages (M Φ ) initiates posttranslational modifications of PPAR γ, that in turn alter its protein function. Using the redox-sensitive GFP2 (roGFP2), we validated oxidizing and reducing conditions following classical and alternative activation of M Φ, while the redox status of PPAR γ was determined via mass spectrometry. Cysteine residues located in the zinc finger regions (amino acid fragments AA 90-115, AA 116-130, and AA 160-167) of PPAR γ were highly oxidized, accompanied by phosphorylation of serine 82 in response to LPS/IFN γ, whereas IL4-stimulation provoked minor serine 82 phosphorylation and less cysteine oxidation, favoring a reductive milieu. Mutating these cysteines to alanine to mimic a redox modification decreased PPAR γ -dependent reporter gene transactivation supporting a functional shift of PPAR γ associated with the M Φ phenotype. These data suggest distinct mechanisms for regulating PPAR γ function based on the redox state of M Φ .